Acute coronary syndromes in anaemic patients: the bad or the ugly?. (26th April 2021) - Saleiro, C; De Campos, D; Lopes, J; Sousa, JP; Puga, L; Gomes, ARM; Quefi, S; Cristovao, C; Fernandes, D; Costa, M; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with anaemia are at increased risk of composite cardiovascular (CV) events and all-cause mortality. However, anaemia poses a challenge to doctors when in the context of an acute coronary syndrome (ACS) and the urge to offer intervention treatment and therefore antiplatelet therapy. Purpose: To study the prognostic impact of anaemia in a population with ACS. Methods: 436 ACS patients admitted to a single coronary care with anaemia (male gender, haemoglobin [Hb] <13 g/dL; female gender, Hb < 12 g/dL) who were discharged from hospital were included. The primary endpoint was long-term all-cause mortality. Cox regression was conducted to evaluate the impact on the primary endpoint. The median of follow-up was 36 (± 31) months. Results: Sixty-four percent of the patients were male, with a mean age 75 ± 10 years old. The majority (47%) was admitted with non-ST elevation myocardial infarction. Most of them had previous history of hypertension (87%), dyslipidaemia (63%) and chronic kidney disease (58%), while a minority had a diagnosis of diabetes mellitus (46%). Most of the patients remained in Killip-Kimbal class I throughout hospital-stay. Coronary angiography was not conducted in 15% of the patients. Thirty-six percent of the patients were conservatively treated (not submitted to percutaneous coronary intervention or coronary artery bypass graft). At discharge, 1% of the patients had no antiplatelet or anticoagulation therapy prescribed; 7% had simple antiplatelet therapy; 1% only had anticoagulation therapy; 67% had double antiplatelet therapy; 1% had double therapy (anticoagulation plus a single antiplatelet agent) and 5% had triple therapy (anticoagulation plus two antiplatelets agents); missing data about therapy at discharge in 18% of the patients. 224 patients met the primary outcome. In univariate analysis, nor antiplatelet neither anticoagulation strategies were related to the outcome (P = 0.59; P = 0.73, respectively). In a multivariable model adjusted for age, Hb level, glomerular filtration rate, heart failure diagnosis, left ventricular function (3 categories), maximum troponin I and treatment option (conservative vs revascularization), Hb level remains an important prognosis predictor (HR 0.86, 95% CI 0.77-0.97, per each g/dL increase). In this model, besides from Hb level, only age (HR 1.04, 95% CI 1.02-1.05) and moderate to severely impaired LV function (HR 1.91, 95% CI 1.38-2.63) remained associated with the outcome. Conclusion: The outcome attributed to anaemia patients seems to be independent of treatment strategies and it is related to the Hb level itself. This reinforces the need to explore reversible causes of anaemia, as small increases in Hb level may have a major impact on the prognosis of these patients.